Exploring environmental Kuznets curve. An investigation on EU economies - Badulescu, Daniel; Badulescu, Alina; Simut, Ramona; Bac, Dorin; Iancu, Elena-Ana; Iancu, Nicolaie (Technological and Economic Development of Economy, 2020)
Designing and implementing relevant and effective environmental policies and fostering green and environmental-friendly approaches and behaviors are constant aims for policy makers all over the world. Concurrently, implementing environmental policies involves significant economic and financial efforts, in order to repair environmental damage and to prevent future negative environmental consequences. How effective are the environmental expenditures and how are they related to the economic growth, i.e. the GDP level, are issues of major concern at a governmental level. In this article we are examining the relation between GDP and environmental expenditure, by using statistical data available for EU economies, for the time period 1995-2013. We found that the Environmental Kuznets Curve hypothesis is supported in most of the EU economies, both for government environmental protection and specialized providers, public and private environmental protection. Further and deeper analyses performed showed different situations for specific countries and even a negative relation between GDP and government environmental protection for specific cases.First published online 18 November 2019